Synergistic effect and antibiofilm activity of the antimicrobial peptide K11 with conventional antibiotics against multidrug-resistant and extensively drug-resistant Klebsiella pneumoniae - Chatupheeraphat, Chawalit; Peamchai, Jiratchaya; Luk-in, Sirirat; Eiamphungporn, Warawan (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Infections caused by drug-resistant Klebsiella pneumoniae are now a serious problem for public health, associated with high morbidity and mortality due to limited treatment options. Therefore, new antibacterial agents or a combination of agents as the first line of treatment are urgently needed. K11 is a novel antimicrobial peptide (AMP) that has demonstrated in vitro antimicrobial activity against several types of bacteria. Additionally, K11 has previously shown no hemolytic activity. Herein, the antibacterial activity, the synergistic action of K11 in combination with different conventional antibiotics and the antibiofilm activity of K11 against multidrug-resistant (MDR) and extensively drug-resistant (XDR) K. pneumoniae were investigated. Meanwhile, the stability and ability to induce the bacterial resistance of K11 were also tested. Methods Fifteen clinical isolates of MDR/XDR K. pneumoniae were used in this study. The minimum inhibitory concentration (MIC) of K11 against these isolates was determined by the broth microdilution method. In vitro synergy between K11 and antibiotics was evaluated using the checkerboard methodology. The antibiofilm activity of K11 against K. pneumoniae strong biofilm producers were explored by the crystal violet staining. The stability in different environments and resistance induction of K11 were evaluated by MIC determination. Results The MIC values of K11 against MDR/XDR K. pneumoniae isolates were 8-512 μg/mL. Intriguingly, the synergistic effects were clearly observed for K11 in combination with chloramphenicol, meropenem, rifampicin, or ceftazidime, whereas no synergy was observed when K11 was combined with colistin. Besides, K11 effectively prevented biofilm formation against K. pneumoniae strong biofilm producers in a concentration-dependent manner starting at 0.25×MIC and exerted an enhancing effect when administered in combination with meropenem, chloramphenicol, or rifampicin. Additionally, K11 demonstrated high thermal and wide pH stability along with good stability in serum and physiological salts. Significantly, K. pneumoniae showed no induction of resistance even after prolonged exposure to a sub-inhibitory concentration of K11. Conclusion These findings indicate that K11 is a promising candidate with potent antibacterial and antibiofilm activities without inducing resistance and acts synergistically with conventional antibiotics against drug-resistant K. pneumoniae.